Lactobacillus plantarum PFM 105 Promotes Intestinal Development Through Modulation of Gut Microbiota in Weaning Piglets - Wang, Tianwei; Teng, Kunling; Liu, Yayong; Shi, Weixiong; Zhang, Jie; Dong, Enqiu; Zhang, Xin; Tao, Yong; Zhong, Jin (Frontiers in Microbiology, 2019)
Lactobacillus plantarum is a widespread bacterial species and is commonly used as a probiotic. L. plantarum PFM105 was isolated from the rectum of a healthy sow. Here we found that L. plantarum PFM105 showed probiotic effect on weaning piglets in which intestinal inflammation and unbalanced gut microbiota happened frequently. L. plantarum PFM105 was identified to improve the growth of weaning piglet and promote the development of small intestinal villi. Antibiotics are often used in weaning piglet to prevent intestinal infection and promote the growth of animal. We found that weaning piglets feeding with L. plantarum PFM105 showed similar growth promotion but decreased diarrhea incidence compared with those feeding with antibiotics. High-throughput sequencing was used to analyze the gut microbiota in weaning piglets treated with L. plantarum PFM105 or antibiotics. The relative abundance of beneficial microbes Prevotellaceae and Bifidobacteriaceae were increased in colon of weaning piglet feeding L. plantarum PFM105, while antibiotics increased the relative abundance of bacteria associated with pathogenicity, such as Spirochaeta and Campylobacteraceae. L. plantarum PFM 105 increased indicators of intestinal health including serum levels of IgM, IL-10, and TGF-β, and colonic levels of SCFAs. We found strong correlations between the alterations in gut microbiota composition caused by feeding antibiotics and probiotics and the measured growth and health parameters in weaning piglets. The addition of L. plantarum PFM105 could significantly increase the relative abundance of metabolic genes which may important to intestinal microbiota maturation. Altogether, we demonstrated here that L. plantarum PFM 105 could promote intestinal development through modulation of gut microbiota in weaning piglets.